Volume atrial esquerdo de felinos domésticos aparentemente saudáveis: comparação entre dois métodos ecocardiográficos - Schulien, Tatiana (2017)
Cardiomyopathies represent elevated morbidity and mortality among cats. Echocardiography is the most indicated exam for evaluating these conditions during clinical routine. In the echocardiographic exam, the size of the left atrium (LA) is widely used as representative of the severity of cardiac diseases and as predictor of cardiovascular events, in addition to its use in long term hemodynamic monitoring. Currently, the most indicated form for evaluating atrial size is by means of its volume. The present work had the objective of defining physiological values of the left atrial volume (LAV) of healthy domestic felines (n=32) by means of bidimensional echocardiography, using the monoplane Simpson and Area-Length methods and compare each of them; evaluate the effects of weight, cardiac frequency, age, gender and race over the LAV; evaluate the repeatability reproducibility of the monoplane Simpson and Area-Length methods, as well as the left atrium/aorta relation. The reference interval found for the LAV by the Simpson method was of 0.09-0.33 mL/kg, and for the Area-Length method was of 0.08-0.40 mL/kg. Both methods presented elevated correlation, however with discordant volumes. The only variable to influence the atrial volume was weight. The evaluation of atrial size by volumetric methods presented better repeatability and reproducibility then the traditional left atrium/aorta relation. The results of this research rendered positive perspectives for a better follow-up and therapeutic management of feline cardiopathies by means of a more precise investigation of the LA.